question

Which quadratic equation is equivalent to (x-4)^2 - (x-4) - 6 = 0?

answer

u^2 - u - 6= 0 where u= (x - 4)

question

What substitution should be used to rewrite 4x^12 - 5x^6 - 14 = 0 as a quadratic equation?

answer

u = x^6

question

What substitution should be used to rewrite 6(x + 5)^2 + 5(x + 5) - 4 = 0 as a quadratic equation?

answer

u = (x + 5)

question

What substitution should be used to rewrite 4x^4 - 21x^2 + 20 = 0 as a quadratic equation?

answer

u = x^2

question

Which quadratic equation is equivalent to (x^2 - 1)^2 - 11(x^2 - 1) + 24 = 0?

answer

u^2 - 11u + 24 = 0 where u = (x^2 - 1)

question

What are the solutions of the equation x^4 + 6x^2 + 5 = 0? Use u substitution to solve.

answer

x = +/- square root of -1 and x = +/- square root of -5

question

Which equation is in quadratic form?

answer

10x^8 + 7x^4 + 1 = 0

question

What are the solutions of the quadratic equation (x - 8)^2 - 13(x - 8) + 30 = 0? Use u substitution to solve.

answer

x = 11 and x = 18

question

Which quadratic equation is equivalent to (x + 2)^2 + 5(x + 2) - 6 = 0?

answer

u^2 + 5u - 6 = 0 where u = (x + 2)

question

What are the solutions of the equation x^4 - 5x^2 - 14 = 0? Use factoring to solve.

answer

x = +/- square root of 7 and x = +/- i square root 2